PENGARUH KUALITAS LAYANAN ELEKTRONIK DAN KUALITAS INFORMASI APLIKASI MOBILE ALODOKTER TERHADAP KEPUASAN PENGGUNA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Dana Prasetiyo; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Alodokter's mobile application is one of the best online service providers in Indonesia that provides health service. One of them is to provide the quality of online-based services and the best quality of information to consumers. Both of these methods are stated to be able to make consumers not move to other parties and provide user satisfaction for consumer. This research is based on the stimulus-response theory that describes communication as a simple process of action and reaction, starting from the stimulus and ending with a response. The purpose of this study is to determine whether there is an influence qualityof electronic service and the quality of information on alodokter mobile applications to user satisfaction on students of the Faculty of Medicine, University of Riau. The method used in this study is the quantitative explanatory method. The data collection technique in this study uses a questionnaire with a sample of 174 respondents taken based on the accidental random sampling technique. To find out whether there is an influence of independent variables on the dependent variable, the researcher uses multiple linear regression analysis, t test, F test and coefficient of determination test with the help of SPSS version 20. Based on multiple linear regression analysis, the research regression equation is Y: 1,963 + 0,083X1 + 0,175X2. Through the t test and F test, the significance value for each test is smaller than α = 0.05. The coefficient of determination test in the result is 62, 2% which is in the high category. Wich meanss there is high influence qualityof electronic service and the quality of information on alodokter mobile applications to user satisfaction on students of the Faculty of Medicine, University of Riau.